EFEKTIFITAS PENGGUNAAN MEDIA YOUTOBE TERHADAP HASIL BELAJAR MATEMATIKA SMP NEGERI 2 PAREPARE - Nirmalasari Nirmalasari (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2024)
This research aims to determine the effectiveness of using the YouTube application in mathematics learning for class VIII UPTD students at SMP Negeri 2 Parepare. This type of research is Pre-Experimental. The sample for this research was students of class VIII UPTD SMP Negeri 2 Parepare in the odd semester of the 2021/2022 academic year using a sampling technique, namely cluster random sampling. Data collection was carried out using research instruments in the form of test sheets, student activity observation sheets, teacher ability observation sheets to manage learning and student response questionnaire sheets. The results of the research show that learning using YouTube media is effective in mathematics learning for class VIII students at UPTD SMPN 2 Parepare. This is shown by descriptive analysis, namely (1) student learning completeness is included in the